HOMESCHOOLING; An Alternative Islamic Education Institution in Muslim Family - Ilman Nafi'a; Septi Gumiandari (Edueksos: Jurnal Pendidikan Sosial & Ekonomi, 2021)
ABSTRACTThis study aims to explain how homeschooling concept can be an alternative Islamic educational institution in the Muslim family. This study used qualitative methodology with a literature approach. The results showed that (1) Homeschooling is not a new issue in Islamic education. Rasulullah is an originator of homeschooling-based education. The education process was carried out by the Rasulullah at Arqam's house where Rasulullah educated many of his friends and gave birth to many students of extraordinary abilities; (2) There are 3 types of homeschooling in the Islamic tradition: single homeschooling (family), compound homeschooling (halaqah), and homeschooling communities (mosque); (3) Homeschooling based on fitrah education contains monotheism, religious, moral, leadership, and vocational educations; (4) There are seven aspects that must be a concern in family education such as faith, morals, physical, intellectual, psychological, social, and sexual aspects; and (5) To internalize these seven aspects of education, it is necessary to use several methods: education by examples, customs, giving advices, attentions, rewards and punishments.Key Words: Â Homeschooling, Family, and Islamic Education